The Impact Of Environmental Degradation On Human Health And Its Relevance To The Right To Health Under International Law - Gwangndi, Maryam Ishaku; Muhammad, Yahaya Abubakar; Tagi, Sule Musa (European Scientific Journal, ESJ, 2016)
When natural habitats are destroyed or natural resources are depleted the environment is degraded. Environmental degradation results from factors such as urbanisation, population growth, intensification of agriculture, rising energy use and transportation, climate change, pollutions arising from many sources such as technological activities. It is explored that as a result of the dynamic interplay of socio-economic factors and technological activities amongst many other factors, these have devastating consequences on human health. Thus environmental degradation consequences affect the health and the right to health of the people. Using the doctrinal method of research, we examine the confluence of environmental degradation and health from a rights perspective. An unhealthy environment possess health hazards consequently a violation of the right to health. The article recommends that states’ obligation under international law to protect the right to health should be enforceable. Human beings are entitled to right to health even as the environment needs to be protected from activities which cause environmental degradation.